THE IMPLEMENTATION OF THE PROBLEM-BASED LEARNING METHOD TO ENHANCE GRADE 7 STUDENTS’ CRITICAL THINKING SKILLS IN LEARNING MATHEMATICS AT SMP HOLLAND VILLAGE MANADO - Oktapratama, Ryan; Chrismastianto, Imanuel Adhitya Wulanata; Hidayat, Dylmoon (Universitas Pelita Harapan, 2019)
Critical thinking is one of the most important issues in education. However, based on field observation results it is found that students have low critical thinking skills. One reason is that learning activities in the classroom do not foster students’ critical thinking skills. The purpose of this research study to enhance students’ critical skills by implementing the Problem-based Learning (PBL) method. The research subjects were 29 grade 7 students in a junior high school in Manado. The research method used was Classroom Action Research (CAR), conducted from September 12 to November 3, 2017. The instruments used were diagnostic tests, pre-tests and post-tests, observation sheets, student interviews, checklists by observers and students, and the researcher’s reflection journal. Data results were analyzed using the descriptive qualitative method. The results showed that the implementation of the PBL method was able to enhance students’ critical thinking skills in learning math with the achievement percentage of students who passed the KKM for pre-test and post-test based on the overall data analysis result from cycle one to two showing an enhancement of 22% on the first indicator, 9% on the third indicator, and 2% on the fourth indicator. The second indicator showed no enhancement amd there was a decrease of 8% on the fifth indicator. Therefore, the PBL method is effective in enhancing students’ critical thinking skills through each stage of the method in the learning process.BAHASA INDONESIA ABSTRACT: Kemampuan berpikir kritis adalah salah satu hal terpenting dalam dunia pendidikan. Namun, berdasarkan observasi di lapangan ditemukan bahwa siswa memiliki keterampilan berpikir kritis yang rendah. Salah satu penyebabnya adalah aktivitas pembelajaran di kelas tidak melatih keterampilan berpikir kritis siswa. Adapun tujuan dari penelitian ini untuk meningkatkan keterampilan berpikir kritis siswa menggunakan metode Problem-based Learning (PBL). Subyek penelitian adalah 29 siswa kelas VII di suatu SMP di Manado. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK), dilakukan dari September sampai dengan November 2017. Instrumen yang digunakan adalah diagnostic test, pre-test dan post-test, lembar observasi, wawancara siswa, checklistoleh pengamat dan siswa, dan jurnal refleksi peneliti. Analisis data hasil penelitian menggunakan metode deskriptif kualitatif. Hasil penelitian menunjukkan bahwa penerapan metode PBL mampu meningkatkan keterampilan berpikir kritis siswa dalam pembelajaran matematika dengan peningkatan indikator satu sebesar 22%, indikator tiga sebesar 9%, dan indikator empat sebesar 2%. Adapun untuk indikator dua tidak mengalami peningkatan dan indikator lima mengalami penurunan sebesar 8%. Dengan demikian, metode PBL terbukti efektif meningkatkan keterampilan berpikir kritis siswa melalui setiap tahapan metode dalam proses pembelajaran.